2020
DOI: 10.1101/2020.07.25.20161091
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Baseline Cardiometabolic Profiles and SARS-CoV-2 Risk in the UK Biobank

Abstract: Background SARS-CoV-2 is a rapidly spreading coronavirus with a high incidence of severe upper respiratory infection that first presented in Wuhan, China in December 2019. Many factors have been identified as risk factors for SARS-CoV-2, with much attention being paid to body mass index (BMI), but little investigation has been done to investigate dysregulation of lipid profiles and diabetes, which are often comorbid in high BMI patients. Objective This study seeks to describe the impact of BMI, HDL, LDL, Ap… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…Moreover, an inverse correlation between measured levels of HDL and LDL cholesterol and hospitalizations for infectious disease was detected in 407,558 British individuals in the UK Biobank, whereas genetically determined levels of HDL were also inversely associated with hospitalizations for infections and rates of sepsis-related mortality ( Trinder et al., 2020 ). In agreement with these findings, higher levels of HDL were associated with a reduced risk of COVID-19 infection in the UK Biobank population ( Scalsky et al., 2020 ), whereas low levels of HDL on admission have been associated with greater severity of COVID-19 illness in retrospective observational analyses ( Wang et al., 2020a ).…”
Section: Intracellular and Extracellular Cholesterol Lipids And Stasupporting
confidence: 56%
“…Moreover, an inverse correlation between measured levels of HDL and LDL cholesterol and hospitalizations for infectious disease was detected in 407,558 British individuals in the UK Biobank, whereas genetically determined levels of HDL were also inversely associated with hospitalizations for infections and rates of sepsis-related mortality ( Trinder et al., 2020 ). In agreement with these findings, higher levels of HDL were associated with a reduced risk of COVID-19 infection in the UK Biobank population ( Scalsky et al., 2020 ), whereas low levels of HDL on admission have been associated with greater severity of COVID-19 illness in retrospective observational analyses ( Wang et al., 2020a ).…”
Section: Intracellular and Extracellular Cholesterol Lipids And Stasupporting
confidence: 56%
“…Finally, a study of cardiometabolic profiles in 9005 COVID-19 patients in the UK Biobank showed that T2DM and obesity were associated with significantly increased odds of SARS-CoV-2 infection, while elevated levels of HDL and apolipoprotein A were associated with significantly decreased odds of infection. 27 Interestingly, in this final study, after controlling for HDL, the effects of BMI, T2DM, and hemoglobin A1c lost significance, suggesting that HDL may be a major mediator providing protection against COVID-19. The exact mechanism by which obesity predisposes patients to SARS-CoV-2 infection remains unclear; however, there are some key parameters to consider.…”
Section: Cardiometabolic Disease and Susceptibility To Sars-cov-2 Inf...mentioning
confidence: 73%
“…Thus, serum cholesterol and lipoprotein marker monitoring may have an important clinical value for COVID-19 risk prediction ( 115 ). Increased triglyceride/HDL-C ratios may be useful for the early identification of patients with high risk and poor outcomes ( 245 , 246 ). Moreover, in patients with severe disease, significantly elevated serum HDL levels are associated with favorable outcomes ( 112 ).…”
Section: The Role Of Cholesterol Metabolism During the Coronavirus Li...mentioning
confidence: 99%